It's not all about flagella - sticky invasion by pathogenic spirochetes - Strnad, Martin; Koizumi, Nobuo; Nakamura, Shuichi; Vancová, Marie; Rego, Ryan O M (Trends in parasitology, 2024)
Pathogenic spirochetes cause a range of serious human diseases such as Lyme disease (LD), syphilis, leptospirosis, relapsing fever (RF), and periodontal disease. Motility is a critical virulence factor for spirochetes. From the mechanical perspective of the infection, it has been widely believed that flagella are the sole key players governing the migration and dissemination of these pathogens in the host. Here, we highlight the important contribution of spirochetal surface-exposed adhesive molecules and their dynamic interactions with host molecules in the process of infection, specifically in spirochetal swimming and crawling migration. We believe that these recent findings overturn the prevailing view depicting the spirochetal body to be just an inert elastic bag, which does not affect spirochetal cell locomotion.
Keywords: Host-Pathogen Interactions; Spirochaetales; Flagella; adhesion; spirochetové infekce; Spirochaetales Infections; translational motility; zvířata; Humans; pathogenesis; flagella; interakce hostitele a patogenu; spirochetes; lidé; Animals